Mediator Role of Dissociative Experiences in the Effect of Childhood Traumas on Emotion Regulation Difficulty and Parental Child-Containing Function - Elif Yöyen; Fatih Bal; Tülay Güneri Barış; Meryem Selva Arslan; Gülşen Filazoğlu Çokluk (MDPI AG, 2024)
The aim of this study is to examine the mediating role of dissociation in emotional regulation and parental child-containing function skills of mothers exposed to childhood trauma. The research was conducted with 400 mothers between the ages of 20-60 who had childhood trauma and currently have children between the ages of 0-18. The relational screening model, one of the general screening models, was used in the research. The sample of the research was selected using the convenient sampling method and the simple random method. Research data were collected with the Sociodemographic Information Form, Childhood Trauma Scale (CTS), Parental Child-Containing Function Scale (PCCFS), Emotion Regulation Difficulty Scale (ERDS), and Dissociative Experiences Scale (DES). According to the results obtained in the study, physical abuse (β = 0.197; 95% CI [0.124; 0.268]), physical neglect (β = 0.232; 95% CI [0.161; 0.306]), emotional abuse (β = 0.238; 95% CI [0.169; 0.309]), emotional neglect (β = 0.210; 95% CI [0.150; 0.275]), and sexual abuse (β = 0.139; 95% CI [0.058; 0.220]) were found to have a significant indirect effect on emotion regulation difficulties through dissociative experiences. In addition, physical abuse (β = 0.122; 95% CI [0.071; 0.181]), physical neglect (β = 0.151; 95% CI [0.084; 0.228]), emotional abuse (β = 0.158; 95% CI [0.086; 0.238]), emotional neglect (β = 0.159; 95% CI [0.093; 0.235]), and sexual abuse (β = 0.086; 95% CI [0.039; 0.150] was found to have a significant indirect effect on parental child-containing function skills through dissociative experiences.